Wheat blast - Kumar, Sudheer, 1972-; Kashyap, Prem Lal, 1981-; Gyanendra Singh (Boca Raton, FL : CRC Press, 2020)
"Wheat Blast provides systematic and practical information on wheat blast pathology, summarises research progress and discusses future perspectives based on current understanding of the existing issues. The book explores advance technologies that may help in deciding the path for future research and development for better strategies and techniques to manage the wheat blast disease. It equips readers with basic and applied understanding on the identification of disease, its distribution and chances of further spread in new areas, its potential to cause yield losses to wheat, the conditions that favour disease development, disease prediction modelling, resistance breeding methods and management strategies against wheat blast. Features: Provides comprehensive information on wheat blast pathogen and its management under a single umbrella Covers disease identification and diagnostics which will be helpful to check introduction in new areas Discusses methods and protocol to study the different aspects of the disease such as diagnostics, variability, resistance screening, epiphytotic creation etc. Gives deep insight on the past, present and future outlook of wheat blast research progress This book's chapters are contributed by experts and pioneers in their respective fields and it provides comprehensive insight with updated findings on wheat blast research. It serves as a valuable reference for researchers, policy makers, students, teachers, farmers, seed growers, traders, and other stakeholders dealing with wheat"--
Wheat blast -- A global threat to wheat production -- Population biology of wheat blast pathogen -- Identification and diagnosis of wheat blast -- The infection process of Magnaporthe oryzae Triticum on wheat -- Genetic and molecular basis of Wheat -- Magnaporthe oryzae Triticum interaction -- Ecology and epidemiology of wheat blast -- Effect of blast on wheat physiology -- Screening for wheat germplasm for blast resistance: Methods and Protocols -- Breeding for Wheat Blast Resistance -- Integrated management of wheat blast disease.
OCLC-licensed vendor bibliographic record.
Keywords: Wheat -- Diseases and pests -- Control; SCIENCE / Life Sciences / Botany